2018
DOI: 10.4212/cjhp.v71i3.2582
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Extemporaneously Compounded Domperidone 5 mg/mL Suspension in Oral Mix in Plastic and Glass Bottles and Plastic Syringes

Abstract: <p>ABSTRACT</p><p>Background: Domperidone liquid for oral administration is not commercially available in Canada, but is needed for patients who cannot swallow intact tablets.</p><p>Objective: To evaluate the stability of domperidone 5 mg/mL suspensions prepared in Oral Mix vehicle and stored, for up to 91 days, in amber polyvinylchloride (PVC) bottles, amber glass bottles, or amber poly - ethylene terephthalate (PET) bottles at 4°C or 25°C or in polypropylene oral syringes at 25°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Suspensions are a liquid form of medication containing finely divided insoluble therapeutically active ingredients dispersed uniformly throughout the suspending medium (47). Suspension can be stable for 30-90 days depending on preparation (48,49). Data on suspensions are quite limited, with only a few formal studies on the palatability and stability of different suspensions reported in the literature (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Suspensions are a liquid form of medication containing finely divided insoluble therapeutically active ingredients dispersed uniformly throughout the suspending medium (47). Suspension can be stable for 30-90 days depending on preparation (48,49). Data on suspensions are quite limited, with only a few formal studies on the palatability and stability of different suspensions reported in the literature (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The research laboratories of Ron Donnelly at The Ottawa Hospital, Dr Mary Ensom at the British Columbia Children's Hospital, and Scott Walker at Sunnybrook Health Sciences Centre have provided, through their articles in CJHP, much useful information that allows practitioners to understand what storage conditions are acceptable for drug formulations beyond the commercially available products. For example, this issue contains an article about the stability of an extemporaneous formulation of domperidone, 1 and the Journal's Editorial Board continues to welcome such research for publication. But why?…”
Section: Glen Brownmentioning
confidence: 99%